Neutral cis-alkyl olefin rhodium(I) complexes: models of intermediates in late transition metal olefin polymerization with surprising structure - Urtel, Heiko; Meier, Claudia; Rominger, Frank; Hofmann, Peter (Organometallics, 2010)
The reaction of the γ-agostic 14 VE complex [(κ2-dtbpm)Rh(Np)] (1) with olefins opened an access to neutral, cis-alkyl olefin complexes (κ2-dtbpm)Rh(Np)(η2-olefin) (2a/b, Np = neopentyl, olefin = ethylene, methylacrylate) bearing the cis chelating bisphosphine ligand dtbpm (bis(di-tert-butylphosphino)methane, tBu2P-CH2-PtBu2). They represent the first structurally characterized examples of neutral Rh systems with cis bisphosphine ligation, isoelectronic to the presumed resting states in late transition metal (e.g., Pd, Ni) catalyzed polymerization reactions. Their solid-state molecular structures revealed an unexpected, non-square-planar coordination mode of the olefin moiety, with the center of the C═C double bond moved 34° out of the P2RhCNp plane. In solution rapid dynamic processes interconvert equivalent structures with the olefin above or below this plane. DFT and QM/MM (ONIOM) calculations reproduce correctly the minimum geometries found in the crystal structures. They are caused by electronic effects, as shown by fragment MO (NBO analysis) and frontier MO arguments. The unusual structure motif carries over to the chloro complexes (κ2-dtbpm)Rh(Cl)(η2-olefin) (5a/b, olefin = fumaronitrile, acrylonitrile). No polymerization is observed when 2a is exposed to an excess of ethylene, indicating a rather high olefin insertion barrier for this uncharged RhI species, in agreement with DFT calculations of the transition state for ethylene insertion into the Rh−CNp bond of (κ2-dhpm)Rh(Np)(η2-C2H4) (2a*). This contrasts with the high catalytic activity of isolectronic NiII and PdII systems.
Der Artikel ist Teil der Dietmar Seyferth Festschrift
Gesehen am 16.02.2024